Characterization of Perturbing Actions by Verteporfin, a Benzoporphyrin Photosensitizer, on Membrane Ionic Currents - Huang, Mei-Han; Liu, Ping-Yen; Wu, Sheng-Nan (Frontiers in Chemistry, 2019)
Verteporfin (VP), a benzoprophyrin derivative, has been clinically tailored as a photosensitizer and recently known to suppress YAP-TEAD complex accompanied by suppression of the growth in an array of neoplastic cells. However, the detailed information is little available regarding possible modifications of it and its related compounds on transmembrane ionic currents, despite its growing use in clinical settings. In this study, from whole cell recordings, VP (0.3-100 M) increased the amplitude of Ca2+-activated K+ currents (IK(Ca)) in pituitary tumor (GH3) cells in a concentration-dependent manner with an EC50 value of 2.4 M. VP-stimulated IK(Ca) in these cells was suppressed by further addition of either paxilline, iberiotoxin or dithiothreitol, but not by that of tobultamide or TRAM-39. VP at a concentration of 10 M mildly but significantly suppressed the amplitude of delayed-rectifier K+ current; however, it had minimal effects on M-type K+ current. In cell-attached current recordings, addition of VP to the recording medium enhanced the activity of large-conductance Ca2+-activated K+(BKCa) channels. In the presence of VP, additional illumination with light intensity of 5.5 mW/cm2raised the probability of BKCa-channel openings further. Addition of VP decreased the peak amplitude of L-type Ca2+ current together with slowed inactivation time course of the current; however, it failed to modify voltage-gated Na+ current. Illumination of GH3 cells in continued presence of VP also induced a non-selective cation current. Additionally, VP increased the activity of BKCa channels in human 13-06-MG glioma cells with an EC50 value of 1.9 M. Therefore, the effects of VPon ionic currents described herein tend to be upstream of its inhibition of YAP-TEAD complex and they are conceivably likely to contribute to the underlying mechanisms through which it and its structurally similar compounds effect the modifications in functional activities of pituitary or glial neoplastic cells, if the in vivo findings occur.